Sacituzumab govitecan response in extensive leptomeningeal carcinomatosis from triple-negative breast cancer: a case report - Yaringaño, Jesús; Roca-Herrera, María; Eremiev, Simeón; Mascaró-Baselga, Pau; Benito, Pau; Núñez, Fidel; Benavente, Sergi; Pimentel, Isabel (Frontiers in Oncology, 2024)
Sacituzumab Govitecan (SG), a Trop-2-directed antibody-drug conjugate (ADC), was the first ADC approved for patients with metastatic triple negative breast cancer (mTNBC) who had received at least two prior lines of therapy for advanced disease. Although SG has shown promising clinical activity in treating brain metastases in both ASCENT randomized trial and real-world analysis, its utility in leptomeningeal carcinomatosis (LC) remains underexplored. We report the diagnostic and therapeutic process of a patient, who develops extensive LC from TNBC treated with SG. She presented clinical response after the first cycle of SG with a PFS of 6 months. This case report highlights the need for further inquiry into the use of SG in LC.